Effects of Gymnema lactiferum leaves on glycemic and lipidemic status in type 2 diabetes subjects - Thushari Bandara; Begum Rokeya; Sakina Khan; Liaquat Ali; Sagarika Ekanayake; Errol R. Jansz; Kandiah Balasubramanium (Bangladesh Pharmacological Society, 2009)
Gymnema lactiferum var. lactiferum is a climber distributed in many South Asian countries. It is reported that the diabetic patients in Sri Lanka use G. lactiferum leaves as a treatment for diabetes. However, scientific data is not available on this plant. A clinical trial was conducted including 26, type 2 diabetic patients with hypercholesterolemia. The treatment group received a suspension of G.  lactiferum leaf powder twice daily for  four weeks. Blood parameters of both groups (treated and control) were determined at the beginning and the end of the study period. Study indicates significant effects on fasting blood sugar (p=0.002), cholesterol (p=0.004), and LDL lowering (p=0.023) and a significant postprandial glucose lowering effect (p=0.026 for 60 min and p=0.022 for 120 min, after four weeks). In spite of the short study period, a significant reduction (p=0.012) in HbA1C levels was also observed.